Pengembangan Kelembagaan Dalam Optimalisasi Potensi Desa Pada Kelompok Sadar Wisata (POKDARWIS) di Desa Winduaji Kecamatan Paguyangan Kabupaten Brebes - Chamid Sutikno; Zaula Rizqi Atika; Mujib Mujib (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Indonesia as a country that has geographical diversity, regional characteristics and culture, makes it Indonesia's potential, especially in the tourism sector. The existence of unique and interesting tourism potential in an area should be utilized through good tourism development. However, the tourism industry in Indonesia is only at the stage of development where the stage itself is only concentrated in a few areas. For this reason, the government continues to encourage areas with tourism potential, one of which is by promoting the Pokdarwis (Tourism Awareness Group) program. The penjalin reservoir is located in Winduaji village, Kec. Paguyangan, Kab. Brebes is an icon for the village of Winduaji which ultimately inspires the community to form a tourism awareness group. However, due to limited resources, this pokdarwis winduaji has not been able to maximize tourism potential properly. Based on this, the presence of community service regarding